Catherine I: «Tsarina-Assistant»: to typology of women-rulers of the New Age in Russia - O. N. Mukhin (Омский научный вестник: Серия "Общество. История. Современность")
Information in the historiography about the main milestones of the biography of Catherine I and ideas about the peculiarities of her relationship with Peter I are subjected to critical analysis. Based on the achievements of psychology, an explanation is offered for raising a low-born woman to the rank of official spouse by the king-reformer. An attempt is being made to determine the «typological» place of Catherine I among the Russian sovereigns of the New Age, for which the concept of «Tsarina -Assistant» is proposed and characterized, denoting the type of monarch’s wife, which first representative was Catherine and which, after the era of palace coups, will become the norm in the Russian Empire